Analisis Pengaruh Investasi, Tenaga Kerja, dan Upah Minimum Provinsi terhadap PDRB Industri Pengolahan di Provinsi Jambi - Zahra Septira; Etik Umiyati; Rahma Nurjanah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine the development and analyze the effect of investment, labor force, and provincial minimum wage on the Gross Regional Domestic Product (GRDP) of the manufacturing industry sector in Jambi Province during the period 1995–2024. The data used in this study are secondary data obtained from the Central Bureau of Statistics (BPS) of Jambi Province. This research employs a descriptive quantitative approach using multiple linear regression analysis through the Cobb-Douglas production function model. The results of the study show that (1) the average growth of the manufacturing industry’s GRDP in Jambi Province during the period 1995–2024 was 4.80 percent; investment grew by 11.12 percent, labor force by 1.8 percent, and UMP by 13.1 percent; and (2) the results of multiple linear regression analysis indicate that investment, labor force, and UMP variables have both partial and simultaneous positive and significant effects on the GRDP of the manufacturing industry sector in Jambi Province.